2010
DOI: 10.1523/jneurosci.3959-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Phase Response Curve Analysis of a Full Morphological Globus Pallidus Neuron Model Reveals Distinct Perisomatic and Dendritic Modes of Synaptic Integration

Abstract: Synchronization of globus pallidus (GP) neurons and cortically entrained oscillations between GP and other basal ganglia nuclei are key features of the pathophysiology of Parkinson's disease. Phase response curves (PRCs), which tabulate the effects of phasic inputs within a neuron's spike cycle on output spike timing, are efficient tools for predicting the emergence of synchronization in neuronal networks and entrainment to periodic input. In this study we apply physiologically realistic synaptic conductance i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
60
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 82 publications
3
60
1
Order By: Relevance
“…Furthermore, the iPRC may not accurately describe the response to larger inputs, perhaps not even to inputs as large as a unitary synaptic potential (Acker et al 2003;Netoff et al 2005b). In addition, synaptic potentials are generated by conductance changes, often at electrotonically distant sites on dendrites, whose effects may not be well represented by the effect of current injected at the soma (Goldberg et al 2007;Schultheiss et al 2010). Finally, inputs activating NMDA-type glutamate receptors (NMDARs) can be expected to pose special problems for the iPRC description, because the NMDAR conductance is prolonged and is a nonlinear function of membrane potential.…”
mentioning
confidence: 99%
“…Furthermore, the iPRC may not accurately describe the response to larger inputs, perhaps not even to inputs as large as a unitary synaptic potential (Acker et al 2003;Netoff et al 2005b). In addition, synaptic potentials are generated by conductance changes, often at electrotonically distant sites on dendrites, whose effects may not be well represented by the effect of current injected at the soma (Goldberg et al 2007;Schultheiss et al 2010). Finally, inputs activating NMDA-type glutamate receptors (NMDARs) can be expected to pose special problems for the iPRC description, because the NMDAR conductance is prolonged and is a nonlinear function of membrane potential.…”
mentioning
confidence: 99%
“…Phase response analysis during in vivo-like high conductance states; dendritic SK determines the mean and variance of responses to dendritic excitation We also demonstrated that synaptic excitation of the distal dendrite can paradoxically delay subsequent spiking when delivered at some phases of the spike cycle (yielding a type II PRC) as a consequence of dendritic activation of the small conductance calcium-activated potassium current, SK 1 . Since during high conductance states spike timing is determined by a balance between intrinsic mechanisms and synaptic input fluctuations, in this study we investigated how somatic and dendritic phase response properties of the GP model are affected by ongoing stochastic synaptic background activity.…”
mentioning
confidence: 89%
“…Related models picked up those ideas and investigated different connectivity changes and their effects on activity (e. g., Kumar et al [2011]). Later, when it became clear how important the intrinsic oscillatory nature of basal ganglia neurons is , models using phase response curves (PRCs) became established (e. g., Schultheiss et al [2010Schultheiss et al [ , 2012, Wilson et al [2011], Holt and Netoff [2014]) which described the reactions of oscillating systems on inputs. Finally, in the last years, models of microcircuitries, for example in striatum [Gittis et al, 2011, Damodaran et al, 2015, have been investigated.…”
Section: How Can Computational Modeling Help To Understand Those Actimentioning
confidence: 99%
“…These channels are assumed to contribute to the firing dynamics in most excitable cells [Bond et al, 1999] and can modulate plasticity [Woodward et al, 2010]. Studies with brain slices of healthy rats [Deister et al, 2009] and computational models of GPe neurons [Deister et al, 2009, Schultheiss et al, 2010 proposed a mechanism of decorrelation via an SK current. Deister et al [2009] showed that rat GP neurons express functional SK channels that contribute to the precision of autonomous firing in GP neurons, and strong SK currents can decrease the sensitivity of GPe neurons to smaller synchronized inputs [Deister et al, 2009].…”
Section: Sk Channel Expressionmentioning
confidence: 99%
See 1 more Smart Citation